دراسة مقارنة لمحاسبة الادوات المالية بين المعيار Ifrs 9 والمعيار Ias 39، ومتطلبات التطبيق في الجزائر - بن سعيد, أمين; عبد الرحيم, نادية; صالحي, بوعلام (جامعة الوادي - University of Eloued, 2021)
تتناول هذه الورقة البحثية الأدوات المالية ومعالجتها المحاسبية حسب كل من المعيارين الدوليين IFRS 9 وIAS 39 من جهة، والنظام المحاسبي المالي SCF من جهة أخرى. وقد حاولنا من خلال هذه الورقة تسليط الضوء على المستجدات التي جاء بها المعيار IFRS 9 مقارنة بالمعيار القديم IAS 39 سواء فيما يتعلق بتصنيف الأدوات المالية، قياسها، إعادة تصنيفها وأيضا خسارة القيمة. وفي الأخير تعرضنا إلى المعالجة المحاسبية للأدوات المالية وفق SCF، ومنها حاولنا تقديم بعض التوصيات لتحسين وتحديث هذه المعالجة المحاسبية في ضوء المستجدات التي جاء بها المعيار الجديد IFRS 9. This paper is addressed to the financial instruments and their accounting treatment according to IFRS 9 and IAS 39 on the one hand, and the financial accounting system SCF from the other hand. We tried in this paper to shed the light on the updates brought by the new IFRS 9 as compared to the old standard IAS 39, in terms of classification, measurement, reclassification and impairment. Finally, we dealt with the accounting treatment of financial instruments in accordance with the SCF, and from there we tried to provide some recommendations to improve and update this accounting treatment in the light of the developments brought by the new standard IFRS 9.
A comparative study of the accounting of financial instruments between IFRS 9 and IAS 39, and the requirements for application in Algeria
مقال
Keywords: الأدوات المالية ; النظام المحاسبي المالي ; التصنيف ; القياس ; خسارة القيمة; IFRS 9 ; IAS 39